Exploring spatial programming through modularity based evolutionary computation - Riskiyanto, Resza; Wibisono, Ahmad Bayu; Harani, Arnis Rochma (Journal of Architecture and Urbanism, 2025)
The application of evolutionary computing in architecture has advanced beyond active feedback to designers by integrating natural processes with computation to synchronize input from the final solution. Following knowledge in digital morphogenesis, new approaches can be formed by examining design issues deemed non-pragmatic and abstract, such as function in spatial programming. The study presented in this paper explores an approach based on the principle of modularity, which describes a biological system’s ability to organize distinct, independent units to increase the system’s adaptability. By employing modularity in evolutionary computation, we can characterize function as an abstract feature of phenotypes. The basic modularity method is simulated by developing a spatial program with dynamic programmatic functions to see how adaptable units are as spatial program components.